A Comparison of Mandated Versus Volunteer Adolescent Participants in Youth Tobacco Cessation Programs - Houser-Marko, Linda (2011)
A national evaluation of community-based youth cessation programs delivered in group format provided the opportunity to compare mandated and volunteer program participants on demographics, smoking patterns, other health behaviors and motivation to quit. A total of 857 youth participants completed surveys prior to the start of their treatment program. Mandated youth comprised 24% of the sample (n=202). Both bivariate and multivariate comparisons were conducted. Mandated participants reported lower levels of stress, higher extrinsic motivation and lower intrinsic motivation to quit, and were more likely to be in the earlier (precontemplation) stage of readiness to quit. Mandated and volunteer smokers did not differ in their smoking patterns, school-related smoking behaviors, or binge drinking. Rates of smoking, school problems, and binge drinking were higher among cessation program participants than in general samples of youth. Programs with mixed voluntary-mandatory participation may benefit from extra attention to motivational issues.